Experimental Study of Photovoltaic Thermal-Thermoelectric (PVT-TE) Air Collector - Nurul Syakirah Nazri; Ahmad Fudholi; Mohd Hafidz Ruslan; Kamaruzzaman Sopian (Institute of Advanced Engineering and Science, 2018)
In this study, an experimental study has been conducted to determine the performance of the photovoltaic thermal- thermoelectric air collector (PVT-TE) hybrid system. Hybrid system consists of photovoltaic panel (PV) and thermoelectric modules (TEs) that can improve the energy efficiency of the system. The results of output temperature (To) and plate temperature (Tp) obtained from the experiment have been used to determine the performance of this hybrid system. Effect of mass flow rate and radiation intensity is also being investigated. Experimental studies were carried out at 0.02 kg/s and 0.09 kg/s which represent minimum and maximum of mass flow rate, and radiation intensities in the range of 268-922 W/m2.